Threatening others : Nicaraguans and the formation of national identities in Costa Rica - Sandoval García, Carlos (Research in international studies. Latin America series, 2004)
During the last two decades, a decline in public investment has undermined some of the national values and institutions of Costa Rica. The resulting sense of dislocation and loss is usually projected onto Nicaraguan "immigrants." Threatening Others: Nicaraguans and the Formation of National Identities in Costa Rica explores the representation of the Nicaraguan "other" in the Costa Rican imagery. It also seeks to address more generally why the sense of national belonging constitutes a crucial identification in contemporary societies.